Interaction between asymmetrical damping and geometrical nonlinearity in vehicle suspension systems improves comfort - Fernandes, J. C.M. [UNESP]; Gonçalves, P. J.P. [UNESP]; Silveira, M. [UNESP] (Springer Nature, 2020)
This work explores the role of asymmetrical damping and geometrical nonlinearities in the suspension system of a simplified vehicle model in order to improve comfort. Improving comfort for passengers is a constant challenge for the automotive industry. Although technologies have been introduced for this purpose, many vehicles still use suspension systems which are less effective in vibration isolation due to cost restrictions. To improve comfort at relatively low cost, the use of asymmetrical suspension dampers has been explored. It has been shown that different asymmetry ratios can be advantageous to improve comfort at different frequency ranges. Models which include the suspension geometry can help to better understand the vehicle dynamical response, as it also depends on the geometrical arrangement of its components. As a contribution to the current literature, this paper proposes a study on asymmetrical damping considering a Double Wishbone suspension geometry. A nonlinear single-degree-of-freedom system subject to harmonic base excitation is used. The combination of asymmetry and geometry nonlinearities is investigated for varying asymmetry ratio, geometrical parameters and vehicle velocity. The numerical and experimental results show that the geometrical nonlinearity induces changes in the spring and damping forces because of different inclinations of the spring–damper assembly during expansion and compression, resulting in changes in acceleration amplitude and resonance frequency. This effect is superimposed on the effect of asymmetrical damping coefficient alone, ultimately influencing the acceleration of the suspended mass. Therefore, these two effects must be considered carefully when designing a suspension system with comfort criteria.
Keywords: Asymmetrical damping; Comfort; Geometrical nonlinearity; Vehicle dynamics